2017
DOI: 10.3389/fpsyt.2017.00169
|View full text |Cite
|
Sign up to set email alerts
|

Android Robot-Mediated Mock Job Interview Sessions for Young Adults with Autism Spectrum Disorder: A Pilot Study

Abstract: The feasibility and preliminary efficacy of an android robot-mediated mock job interview training in terms of both bolstering self-confidence and reducing biological levels of stress in comparison to a psycho-educational approach human interview was assessed in a randomized study. Young adults (ages 18–25 years) with autism spectrum disorder (ASD) were randomized to participate either in a mock job interview training with our android robot system (n = 7) or a self-paced review of materials about job-interviewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…To elicit the belief that the robots were behaving and reacting autonomously, we adopted a remote control system similar to those conventionally used in robotics research ( 27 ). The Android robot employed was ACTROID-F (Kokoro Co., Ltd.), a female version of android robot with an appearance similar to that of a real person (see Figure 1 ) ( 28 , 29 ) (i.e., its body is designed to have remarkably similar proportions, facial features, hair texture, and hairstyle to that of a human). ACTROID-F has been previously used to conduct experiments primarily designed to help adolescents with ASD participate effectively in conversational tasks (e.g., job interviews, conversations, and social skills interventions).…”
Section: Methodsmentioning
confidence: 99%
“…To elicit the belief that the robots were behaving and reacting autonomously, we adopted a remote control system similar to those conventionally used in robotics research ( 27 ). The Android robot employed was ACTROID-F (Kokoro Co., Ltd.), a female version of android robot with an appearance similar to that of a real person (see Figure 1 ) ( 28 , 29 ) (i.e., its body is designed to have remarkably similar proportions, facial features, hair texture, and hairstyle to that of a human). ACTROID-F has been previously used to conduct experiments primarily designed to help adolescents with ASD participate effectively in conversational tasks (e.g., job interviews, conversations, and social skills interventions).…”
Section: Methodsmentioning
confidence: 99%
“…Today, artificial social agents have already been used in the medical and health-care fields (e.g., a realistic android is now employed as a trainer for improving social skills for adults with autism spectrum disorder 29 ). It is important for such social agents in use to minimize uncanny feelings with the installation of legitimate kinetic and visual features.…”
Section: Discussionmentioning
confidence: 99%
“…1 . “ACTROID-F” (Kokoro Co. Ltd.) is a female prototype of an android robot designed to replicate an appearance strongly similar to that of a real person (Kumazaki et al 2017a , b , c , d ). Its artificial body is designed with the proportions, facial features, hair color, texture and style as a human.…”
Section: Methodsmentioning
confidence: 99%
“…An advantage of using social robots, compared to computer based interactions, is that individuals can be exposed to a three-dimensional learning experience that more closely resembles situations in real life settings. For, example, in a previous study (Kumazaki et al 2017b ) that used a social robot for mock job interviews, it was found that the participants were exposed to a three-dimensional learning experience that simulated the challenging, and potentially anxiety-provoking situations, of job interviews in a controlled manner. Social robots with varying degrees of similarities to humans have potential to provide support for children with ASD in skill acquisition.…”
Section: Introductionmentioning
confidence: 99%